Determination of the Natural Radioactivity and Hazard Factors Available of the Soft Drinks in the Markets of the Thi-Qar Province, Iraq - Mohammed, Anees (University of Thi-Qar Journal of Science, 2024)
In this research, the radioactivity of a group of soft drinks available in the markets of Thi-Qar Governorate (southern Iraq) was measured. Seven samples were selected, the most available and consumed by people. The idea of ​​the research is to use a gamma spectrometer NaI (Tl) system to study the presence of radioactivity in these seven samples packaged in glass bottles and their counterparts packaged in metal cans for comparison. The results show that the specific activity values for the bottle samples ranged between 15.787 - 20.160 Bq.kg-1 for K-40, while ranging between (0.112 - 1.194) Bq.kg-1 for U-238. As for the third nuclide Th-232, its values were 0.098 - 0.200 Bq.kg-1. On the other hand, the symmetric radioactivity for the can samples was recorded between 17.888 - 20.885 Bq.kg-1, 0.185 - 1.406 Bq.kg-1, and 0.218 - 0.272 Bq.kg-1 for the corresponding three radioactive nuclides K-40, U-238, and Th-232, respectively. The results of the hazard factors show that the maximum value​​ studied was for (Sprite) sample, while the minimum value was for (Seven Up), each for bottle samples. Concerning to the can samples, the maximum value ​​of these hazard factors studied was for the Fanta sample, while the minimum value was for (Dew). Furthermore, all these values of the hazard factors studied were higher for the can samples than for the symmetric bottles, but with a very small increase. All the radioactive factors studied in them were lower than the global